Landscape into Mindscape: Nature Representations in Australian Literature - Ciglar-Žanić, Janja (1999)
Landscape ("nature", "land") continues to loom large in the Australian discourses of history, politics, literature and culture. "Our symbolic other, in Australia, is the land in her many disguises", Kay Schaffer remarks in her Women and the Bush. "The landscape still seems to hold the key to Australian mythologies", is a recent observation of another Australian culturologist (Ross Gibson). It is the aim of this paper to explore the cultural significance of landscape representations in the Australian narrative.
Setting out with the concept of culture as "a production of meaning and value created in the act of social survival", thus possessed of "the social specificity across diverse cultural experiences" (Homi K. Bhabha), the paper will focus on the factors of Australian nature and history which have had bearing on the centrality of landscape in Australian literary tradition as well as on its distinctly Australian cast. The landscape in Australian cultural tradition, it will ge argued, functions as the nexus of a complex network of meanings which have vitally participated in the perception and articulation of Australian national selfhood.
Several moments of consequence will be highlighted: (a) the function of landscape representations in the early stages of white settlement when the imaginative construction of the land serves as a means of coming to terms with the vast and unfamiliar space; (b) the production of the meaning of "land" as a mode of self-cognition and self-expression against the background of an alien nature as well as against ans English parent culture; (c) the ways in which the inherited colonialist mythic and narrative patterns and conventions are translated into an imaginative language distinctive of Australia's specific cultural space and experience. Literary texts from H.Lawson to R.Stow will be drawn upon to demonstrate the critical propositions.
Projekt MZOS
ENG